Estimation of Some Trace Elements and Antioxidant Status in Breast Cancer Patients Undergoing Radiotherapy - Abdul Rahman R. Mahmood (Journal of Global Pharma Technology, 2018)
Breast cancer (BC) is the most prevalent tract cancer in the world, including Iraq. The classified breast tumors to benign, malignant, and radiotherapy. Cancer treatment depends on certain stages such as mastectomy then chemotherapy alone or with radiation therapy or endocrine therapy according to the prognostic features obtained from the pathology report. The present study included 100 females. The women were split into two groups, control group that consisted of 50 apparently healthy females and 50 patients with BC group who undergo the radiotherapy. The current study highlighted on some of the anthropometric measurements, including the oxidative stress index malondialdehyde (MDA), the concentrations of total antioxidant capacity (TAC), serum albumin (Alb), serum uric acid (UA), and finally the concentrations of copper (Cu) and zinc (Zn) as trace elements were measured as well. The results were compared to control. There was a significant variation in MDA and albumin when comparing patient group with control, while uric acid was statistically insignificant when comparing control group with patients group. Cu concentration was statistically high when compared with control group. On the other side, a significant decrease of Zn concentration of patients was observed compared to control group .In this study, the evaluation of these parameters maybe used as a helpful tool in treatment of breast cancer.Keywords: Breast Cancer, Malondialdehyde, Total antioxidant capacity, Copper, Zinc